Uncorrected refractive errors, visual impairment and need for spectacles among children and adolescents in eastern, China - Yue Zhou; Qi Cai; Xiaojuan Chen; Xiaobo Huang; Zhimin Sun; Yu Song; Lele Li; Yan Zhu; Wang Yong; Peirong Lu (PLoS ONE, 2025)
Background Uncorrected refractive errors (URE) are the leading preventable cause of visual impairment (VI) in children globally, with China facing a critical dual challenge of high myopia prevalence and insufficient spectacle coverage among youth. Despite eastern China’s rapid development, population-based data on URE, VI, and need for spectacles remain scarce, particularly regarding the understudied role of anisometropia and subtype-specific refractive risks. This study evaluates these unmet needs to inform targeted interventions. Methods A cross-sectional school-based study was conducted in Nantong, China, including participants 7–19 years of age. All participants underwent assessments of their uncorrected visual acuity, presenting visual acuity (PVA), and best-corrected visual acuity. URE was defined as PVA worse than 0.3 logMAR (6/12 Snellen) with ≥1 line improvement (≥0.1 logMAR) after correction in either eye.VI was defined as PVA < 6/12 in the better eye. Need for spectacles was defined as the total prevalence of refractive error requiring correction, including unmet, under-met, and met needs. Non-cycloplegic autorefraction was assessed for each participant. Results Of the 9,864 participants, 9,438 were included in the analysis. The total prevalence of URE, VI and need for spectacles was 15.7% (95% CI: 15.0–16.5; n = 1,485),4.9% (95% CI: 4.9–5.3; n = 459) and 55.9% (95% CI: 54.9–56.9; n = 5,275), respectively. Multivariate analysis showed that factors such as female sex (aOR: 1.24, 95% CI: 1.09–1.40), wearing spectacles (aOR: 0.16, 95% CI: 0.14–0.19), older age groups (e.g., aOR: 3.92 for 13–14 years), hyperopia (aOR: 13.08, 95% CI: 7.67–22.31), myopia (aOR: 18.65, 95% CI: 12.54–27.77), and anisometropia (aOR: 1.87, 95% CI: 1.64–2.12) were associated with URE. For VI, significant associations included female sex (aOR: 1.20, 95% CI: 0.98–1.47), hyperopia (aOR: 7.23, 95% CI: 1.60–32.61), myopia (aOR: 53.04, 95% CI: 19.68–142.95), and rural residence (aOR: 1.53, 95% CI: 1.25–1.87). Factors such as older age (highest aOR: 11.77 for 19 years), female sex (aOR: 1.58, 95% CI: 1.42–1.77), hyperopia (aOR: 16.56, 95% CI: 10.97–25.01), myopia (aOR: 28.88, 95% CI: 21.83–38.19), astigmatism (aOR: 2.50, 95% CI: 2.22–2.82), and anisometropia (aOR: 1.37, 95% CI: 1.21–1.55) were associated with need for spectacles. Conclusion Although the prevalence of VI among children and adolescents in eastern China was low, the prevalence of URE and the need for spectacles were high. Myopia was the most important risk factor for URE, VI, and need for spectacles, and the impact of anisometropia on URE, VI, and need for spectacles cannot be ignored. Further research on adjusting intervention strategies is needed to eliminate preventable visual impairments.